Clinical Practice Guidelines on Ordering Echocardiography Before Hip Fracture Repair Perform Differently from One Another - Swart, Eric (HSS J, 2020)
BACKGROUND: Osteoporotic hip fractures typically occur in frail elderly patients with multiple comorbidities, and repair of the fracture within 48 h is recommended. Pre-operative evaluation sometimes involves transthoracic echocardiography (TTE) to screen for heart disease that would alter peri-operative management, yet TTE can delay surgery and is resource intensive. Evidence suggests that the use of clinical practice guidelines (CPGs) can improve care. It is unclear which guidelines are most useful in hip fracture patients. QUESTIONS/PURPOSES: We sought to evaluate the performance of the five commonly used CPGs in determining which patients with acute fragility hip fracture require TTE and to identify common features among high-performing CPGs that could be incorporated into care pathways. PATIENTS AND METHODS: We performed a retrospective study of medical records taken from an institutional database of osteoporotic hip fracture patients to identify those who underwent pre-operative TTE. History and physical examination findings were recorded; listed indications for TTE were compared against those given in five commonly used CPGs: those from the American College of Cardiology/American Heart Association (ACC/AHA), the British Society of Echocardiography (BSE), the European Society of Cardiology and the European Society of Anaesthesiology(ESC/ESA), the Association of Anaesthetists of Great Britain and Ireland (AAGBI), and the Scottish Intercollegiate Guidelines Network (SIGN). We then calculated the performance (sensitivity and specificity) of the CPGs in identifying patients with TTE results that had the potential to change peri-operative management. RESULTS: We identified 100 patients who underwent pre-operative TTE. Among those, the patients met criteria for TTE 32 to 66% of the time, depending on the CPG used. In 14% of those receiving TTE, the test revealed new information with the potential to change management. The sensitivity of the CPGs ranged from 71% (ESC/ESA and AAGBI) to 100% (ACC/AHA and SIGN). The CPGs’ specificity ranged from 37% (BSE) to 74% (ESC/ESA). The more sensitive guidelines focused on a change in clinical status in patients with known disease or clinical concern regarding new-onset disease. CONCLUSIONS: In patients requiring fixation of osteoporotic hip fractures, TTE can be useful for identifying pathologies that could directly change peri-operative management. Our data suggest that established CPGs can be safely used to identify which patients should undergo pre-operative TTE with low risk of missed pathology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11420-020-09762-8) contains supplementary material, which is available to authorized users.